2021
DOI: 10.1038/s41467-021-22021-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient restriction synergizes with retinoic acid to induce mammalian meiotic initiation in vitro

Abstract: The molecular machinery and chromosome structures carrying out meiosis are frequently conserved from yeast to mammals. However, signals initiating meiosis appear divergent: while nutrient restriction induces meiosis in the yeast system, retinoic acid (RA) and its target Stra8 have been shown to be necessary but not sufficient to induce meiotic initiation in mammalian germ cells. Here, we use primary culture of mouse undifferentiated spermatogonia without the support of gonadal somatic cells to show that nutrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 77 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…mTOR complexes are known to play a role as amino acid sensors, allowing cancer cells to adapt to the harsh environment by epigenetic shift and metabolic reprogramming [130,131]. This recapitulates the amino acid restriction within the gonad that surrounds germ cells which could explain thereactivation of meiotic genes [87,132]. Notably, chromatin reorganisation can be affected by nutrient availability.…”
Section: Emerging Links Between Meiotic Initiation and Oncogenesismentioning
confidence: 97%
See 4 more Smart Citations
“…mTOR complexes are known to play a role as amino acid sensors, allowing cancer cells to adapt to the harsh environment by epigenetic shift and metabolic reprogramming [130,131]. This recapitulates the amino acid restriction within the gonad that surrounds germ cells which could explain thereactivation of meiotic genes [87,132]. Notably, chromatin reorganisation can be affected by nutrient availability.…”
Section: Emerging Links Between Meiotic Initiation and Oncogenesismentioning
confidence: 97%
“…Interestingly, although meiosis initiation is regulated by multiple signalling pathways within multicellular organisms, it has been reported that nutrient restriction and RA stimulation can activate the meiotic program through activation of a set of key transcription factors in vitro [ 87 ]. This observation is reminiscent of meiosis initiation in yeast, which is primarily nutrient and metabolism-driven.…”
Section: Regulation Of Mammalian Meiotic Initiationmentioning
confidence: 99%
See 3 more Smart Citations